ChemInform Abstract: Complete Switch of Selectivity in the C—H Alkenylation and Hydroarylation Catalyzed by Iridium: The Role of Directing Groups. Issue 15 (24th March 2016) - Kim, Jiyu; Park, Sung‐Woo; Baik, Mu‐Hyun; Chang, Sukbok
Abstract: The direct olefination/hydroarylation of arenes is investigated in the presence of an iridium catalyst.